EFEKTIVITAS PELAKSANAAN GERAKAN DESA MEMBANGUN (GERDEMA) DAN DANA DESA (DD) DALAM MEMBANGUN DESA DI KECAMATAN MALINAU UTARA KABUPATEN MALINAU PROVINSI KALIMANTAN UTARA - Helmi Pandawa (Prima Center Indonesia, 2017)
This research method uses explorative method with inductive approach. To obtain data researcher used data source in the form of person, place, and paper. Data collection techniques that the author use is observation, interview, and documentation. To answer and reveal the problems of the phenomenon that happens, researcher used data analysis in the form of data reduction, data presentation, and data verification. From the data analysis obtained description that, GERDEMA implementation and DD in building the Village in the Malinau Across Village still not fully effective. It can be seen from the indicators of effectiveness obtained by the researcher that the program's success, the success of the target, satisfaction with the program, the level of input and output, and goal attainment thorough is still lacking. Based on the description above, we conclude that the effectiveness of the implementation of the program GERDEMA and DD in building the village need for extra attention by the central government and local governments, especially in financial management, so that the focus of the village development and community empowerment can run effectively.Key Words: Effectiveness, Building Policy, Village Budget Allocation